1997
DOI: 10.3109/00016349709050065
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonographic assessment of cervical dynamics during the third trimester of normal pregnancy

Abstract: There is a direct relationship between both cervical width and length and gestational age and an inverse relationship with cervical length and the duration of labor. Funnelling of the internal os was not a predictor of the early onset of labor. The dimensions and features of the Asian cervix differ from those of the Europeans, and this should be considered when conducting further studies of a similar nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
6
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 6 publications
(10 reference statements)
10
48
6
6
Order By: Relevance
“…After 32 weeks we would recommend separate reference values for nulliparous women and parous women and separate reference values depending on pregnancy week. Our results with regard to cervical length agree with those reported by Tongsong et al 16 and Brieger et al 15 . Tongsong et al 16 found cervical length did not change substantially between 8 and 31 weeks, and thereafter it 52 34 26 46 27 29 21 29 45 33 45 23 9 32 28 27 30 27 29 20 33 28 34 37 25 decreased.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…After 32 weeks we would recommend separate reference values for nulliparous women and parous women and separate reference values depending on pregnancy week. Our results with regard to cervical length agree with those reported by Tongsong et al 16 and Brieger et al 15 . Tongsong et al 16 found cervical length did not change substantially between 8 and 31 weeks, and thereafter it 52 34 26 46 27 29 21 29 45 33 45 23 9 32 28 27 30 27 29 20 33 28 34 37 25 decreased.…”
Section: Discussionsupporting
confidence: 93%
“…In all studies where cervical AP diameter was measured and compared between nulliparous and parous women it tended to be larger in parous women 17,18 , and in all studies AP diameter increased with gestational age 12,15,17,18 . This is in agreement with the present results.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations